HULL REDESIGN AND ITS EFFECT ON THE RESISTANCE OF MANADO PROTOTYPE SMALL PURSE SEINER: Rancang Ulang Desain Lambung dan Pengaruhnya terhadap Tahanan Gerak Kapal Pukat Cincin Kecil Manado - Pamikiran, Revols D. Ch.; Manoppo, Lefrand; Dien, Heffry; Manu, Lusia (Bogor Agricultural University, 2024)
This research aims to determine the effect of redesigning the hull of a small purse seine ship on its motion resistance. The research was carried out using a small purse seine ship prototype in Manado by changing the length-breath-depth ratio based on the main dimensions of the ship, resulting in three new hull designs coded K-0 (prototype), K-1, K-2, and K- 3. Maxsurf modeler and Maxsurf resistance were used to run a simulation set of three loading conditions (light, half, full) and speed (low, medium, high). The research results show that changes in ship hull design affect the resistance and thrust of the ship. There is a difference in resistance between the ship with the redesigned hull and the prototype, where the smallest difference is shown by K-3. In addition to changes in hull design, changes in ship loading conditions, Froude number, and ship speed lead to increases in ship resistance and thrust. Based on the average allowance (sea margin or service margin) in shipping lanes, the need for propulsion power and the number of propulsion power vessels K-0 (prototype) and K-3 are still better than K-1 and K-2. Keywords: purse-seiner, resistance, speed, propulsion